Early initiation of hydroxyurea (hydroxycarbamide) using individualised, pharmacokinetics‐guided dosing can produce sustained and nearly pancellular expression of fetal haemoglobin in children with sickle cell anaemia. (5th July 2021) - Quinn, Charles T.; Niss, Omar; Dong, Min; Pfeiffer, Amanda; Korpik, Jennifer; Reynaud, Mary; Bonar, Holly; Kalfa, Theodosia A.; Smart, Luke R.; Malik, Punam; Ware, Russell E.; Vinks, Alexander A.; et al.
Summary: Hydroxyurea (hydroxycarbamide) is an effective treatment for sickle cell anaemia (SCA), but clinical responses depend primarily upon the degree of fetal haemoglobin (HbF) induction and the heterogeneity of HbF expression across erythrocytes. The number and characteristics of HbF‐containing cells (F‐cells) are not assessed by traditional HbF measurements. Conventional hydroxyurea dosing (e.g. fixed doses or low starting doses with stepwise escalation) produces a moderate heterocellular HbF induction, but haemolysis and clinical complications continue. Robust, pancellular HbF induction is needed to minimise or fully inhibit polymerisation of sickle haemoglobin. We treated children with hydroxyurea using an individualised, pharmacokinetics‐guided regimen starting at predicted maximum tolerated dose (MTD). We observed sustained HbF induction (mean >30%) for up to 6 years, which was not dependent on genetic determinants of HbF expression. Nearly 70% of patients had ≥80% F‐cells (near‐pancellular), and almost half had ≥90% F‐cells (pancellular). The mean HbF/F‐cell content was ~12 pg. Earlier age of initiation and better medication adherence were associated with high F‐cell responses. In summary, early initiation of hydroxyurea using pharmacokinetics‐guided starting doses at predicted MTD can achieve sustained near‐pancellular or pancellular HbF expression and should be considered an achievable goal for children with SCA treated with hydroxyurea at optimal doses. Clinical trial registration number: NCT02286154 (clinicaltrials.gov).